Development and Characterization of Edible Films Based on Gelatin/Chitosan Composites Incorporated with Zinc Oxide Nanoparticles for Food Protection - Bahar, Asrul; Samik, Samik; Sianita, Maria Monica; Kusumawati, Nita; Khafidlah, Ianatul; Muslim, Supari; Auliya, AR. Sella (Universitas Jenderal Soedirman, 2023)
The increase in cases of global environmental pollution due to plastic waste makes the development of biodegradable active packaging very urgent. Gelatin (G), is one of the potential edible film raw materials. However, its weak water barrier and mechanical properties have limited its wide application. The addition of chitosan nanofiber (CHNF) and zinc oxide nanoparticles (ZnONP) is expected to improve the mechanical and barrier properties and present antioxidant and antimicrobial properties to the G film. Characterization results using FTIR, SEM, and DSC showed good compatibility between the G, CHNF, and ZnONP matrix. Meanwhile, the packaging test results confirmed that gelatin, CHNF, and ZnONP-based composite films have the potential to be used as functional materials in food packaging.